Characterization of Selective Antibacterial Peptides by Polarity Index. (1st April 2012) - Polanco, C.; Samaniego, J. L.; Buhse, T.; Mosqueira, F. G.; Negron-Mendoza, A.; Ramos-Bernal, S.; Castanon-Gonzalez, J. A.
Abstract : In the recent decades, antibacterial peptides have occupied a strategic position for pharmaceutical drug applications and became subject of intense research activities since they are used to strengthen the immune system of all living organisms by protecting them from pathogenic bacteria. This work proposes a simple and easy statistical/computational method through a peptide polarity index measure by which an antibacterial peptide subgroup can be efficiently identified, that is, characterized by a high toxicity to bacterial membranes but presents a low toxicity to mammal cells. These peptides also have the feature not to adopt to an alpha-helicoidal structure in aqueous solution. The double-blind test carried out to the whole Antimicrobial Peptide Database (November 2011) showed an accuracy of 90% applying the polarity index method for the identification of such antibacterial peptide groups.